FAKTOR-FAKTOR YANG MEMENGARUHI KONSERVATISME AKUNTANSI - Dewi, Yuvati Karuna; Setijaningsih, Herlin Tundjung (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research aims to explain the effect of Institusional Ownership, audit committee, leverage and information asymmetry on conservatism accounting at industrial sector companies listed in Indonesia Stock Exchange during the period of 2019-2021. There were 75 samples of consumer cyclicals companies that have been previously selected using purposive sampling method with total of 225 data for three years. The hypothesis were tested by using multiple regression to analyze the relationship between the independent and dependent variables. This research data was processed using IBM SPSS 26 and Microsoft Excel 2019. Results shows that institusional ownership, leverage, and information asymmetry has a poritive and significant effect on conservatism accounting, while the audit committe had no significant ieffect on the practice of income smoothing.